PURCHASE DECISION AND CUSTOMER SATISFACTION “KAFE JAMU” IN NGUTER DISTRICT, SUKOHARJO REGENCY - Dian Tri Astuti; Mohamad Harisudin; Raden Rara Aulia Qonita (Faculty of Animal and Agricultural Science, Diponegoro University, 2022)
The establishment of the Jamu Cafe aims to preserve drinking herbal medicine so that adults and young people favor it. On the other side, the marketing mix strategy with consumer orientation conducted by Kafe Jamu has not been maximized. This study aims to identify the characteristics, purchase decisions, and analyze the consumer satisfaction of Kafe Jamu to improve the performance of the attributes of the marketing mix strategy. The data processing and analysis methods used are descriptive analysis, Customer Satisfaction Index (CSI), and Importance Performance Analysis (IPA). The results showed that the CSI value was 78.86%, which means that consumers are satisfied with the quality of products and services provided by Kafe Jamu. Attributes that should be maintained based on IPA are attributes in quadrant II, including taste, availability of parking facilities, availability and cleanliness of toilets, prices offered, room cleanliness, product hygiene, and ease of access. Attributes that must be improved are in quadrant I, including advertising and promotion, signage, service, and speed of serving.